The Impact of Business Strategy and Human Resource Management on the Competitiveness of Millennial Women Micro-Entrepreneurs in Medan - Ritha F. Dalimunthe; Magdalena Linda Leonita Sibarani (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
Poverty has been a major problem for millennial women in North Sumatra and becoming micro-entrepreneurs appears to be an effective solution to overcome it. This study aims to determine the impact of business strategy and human resource management on the competitiveness of small businesses owned by millennial women in Medan City. Respondents in this study were a list of women who owned and ran businesses located in the city of Medan. In total, 77 respondents were involved in this study by considering the aspects of age, last education, length of business, business capital, source of fund, and business sector. Based on the results of questionnaire data processing which was conducted by applying data quality test, descriptive statistical analysis, classical assumption test, multiple linear regression analysis, as well as F and t-test, the study shows that the variables of both business strategy and human resource management simultaneously have certain impacts on the competitiveness of small businesses owned by millennial women in Medan City. Partially, the human resource management variable shows a significant impact while the business strategy variable does not show a significant impact on the subject matter.